First pump–probe–probe hard X‐ray diffraction experiments with a 2D hybrid pixel detector developed at the SOLEIL synchrotron. (19th February 2020) - Bachiller-Perea, Diana; Abiven, Yves-Marie; Bisou, Jérôme; Fertey, Pierre; Grybos, Pawel; Jarnac, Amélie; Kanouté, Brahim; Koziol, Anna; Langlois, Florent; Laulhé, Claire; Legrand, Fabien; Maj, Piotr; et al.
Abstract : A new photon‐counting camera based on hybrid pixel technology has been developed at the SOLEIL synchrotron; it allows the implementation of pump–probe–probe hard X‐ray diffraction experiments for the first time. A benchmark experiment was successfully performed, showing the advantages of the pump–probe–probe scheme. Abstract : A new photon‐counting camera based on hybrid pixel technology has been developed at the SOLEIL synchrotron, making it possible to implement pump–probe–probe hard X‐ray diffraction experiments for the first time. This application relies on two specific advantages of the UFXC32k readout chip, namely its high frame rate (50 kHz) and its high linear count rate (2.6 × 10 6  photons s −1  pixel −1 ). The project involved the conception and realization of the chips and detector carrier board, the data acquisition system, the server with its specific software, as well as the mechanical and cooling systems. This article reports on in‐laboratory validation tests of the new detector, as well as on tests performed at the CRISTAL beamline within the targeted experimental conditions. A benchmark experiment was successfully performed, showing the advantages of the pump–probe–probe scheme in correcting for drifts of the experimental conditions.